EDUCATION IN ANCIENT INDONESIA CULTURE (700-1700) - Kasdi, Aminuddin (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
Within 1359-1364, Hayam Wuruk did a quest monitoring Majapahit, either to the east side, or the west side. From the many objects he visited, in addition to visiting authorities and local villagers, he also visited religious sacred places. Prapanca, who worked as Dharmadyaksa ring Kasogatan was one of the higher authorities in the kingdom who followed him (Pigeaude, 1963, IV, 150-153). The kingâ€™s quest was also followed by many authorities, and they were certainly intellectual prominent figures in their era. The position of saptopapati, for instance, was occupied by those who were entitled to as pangei or sanget. The term was derived from the root words of (V pgat) meaning: putus (Jw) mastery (Van Naerssen, 1933: 239-258). Furthermore, the terms of pgat is also defined by Van Nseassen as notable (Naerssen, 1933: 239-258). Within various epigraphs, authority titled with pamget or samget was under the third position of kingdom higher authority: rakryan katrini, namely rakrayan kartini (three higher authority), rakrayan mamantri I Hino, Rakryan I halu, Rakryan I Siikan. Within Nagarakratagama, pupuh 68, the second syair noted :â€ â€¦ wanten bodda Mahayana pgat/rin tantra yogiswara â€¦ was an expert (Jw. Mumpuni) of Buddha mahyanaâ€™s lesson on Tantra and Yoga â€¦â€ (Pigeadu, 1963: 52). The terms refer to educated people who have comprehensive and mastery knowledge, so that they can take a decision based on their expertise independently, either in the field of science or governmental problems. Accordingly, if they master their knowledge (Jw. Putusing ngilmu), they will have the authority to make decision towards a problem whenever they are needed. The question is: what kind of knowledge, how can they attain it, and where they learn it? In many sources it was known that one kind of education spread within the age was mandala. During his quest, Hayam Wuruk, for example visited mandala segara. The term mandaleng (mandala â€“ ing) was also found in Serat Pararaton. This article focuses on studying education in ancient Indonesia.